2011
DOI: 10.1007/s12199-010-0196-4
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on environmental and behavioral factors related to missed abortion

Abstract: Physical exercise, ventilation, folic acid supplements, and supervisor support were identified as protective factors for the prevention of missed abortion. Advanced age at pregnancy was a risk factor for missed abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 19 publications
0
16
1
Order By: Relevance
“…In contrast to findings from RCTs, non-randomised intervention and cohort studies, the case–control study by Zhang showed a protective dose–response effect of exercise on the odds of miscarriage 5353. Similar to the other study designs, the study by Maconochie (2007) found no association between strenuous exercise (once/week; 2–3/week; >4/week) compared with rare or no exercise and odds of miscarriage (cases, n=603; controls, n=6116; OR 1.00–1.31, 95% CI 0.75 to 2.00, adjusted for year of conception, maternal age, previous miscarriage and previous live birth) 54…”
Section: Resultscontrasting
confidence: 65%
“…In contrast to findings from RCTs, non-randomised intervention and cohort studies, the case–control study by Zhang showed a protective dose–response effect of exercise on the odds of miscarriage 5353. Similar to the other study designs, the study by Maconochie (2007) found no association between strenuous exercise (once/week; 2–3/week; >4/week) compared with rare or no exercise and odds of miscarriage (cases, n=603; controls, n=6116; OR 1.00–1.31, 95% CI 0.75 to 2.00, adjusted for year of conception, maternal age, previous miscarriage and previous live birth) 54…”
Section: Resultscontrasting
confidence: 65%
“…Conceptual framework for the potential mechanistic links between neighborhood land use and public health. a positive effect on mental and physical health (Bowler et al, 2010;Richardson, and Mitchell, 2010;Zhang et al, 2011). Scholars have associated green spaces with decreased risks of cardiovascular and cerebrovascular diseases, missed abortions, low birth weight, cancer, and mental problems (Barton and Pretty, 2010;Dadvand et al, 2012;Richardson and Mitchell, 2010;Gascon et al, 2016;Sugiyama et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We obtain several results that are consistent with previous studies. First, higher abundance of green land would reduce the risk of a diversity of diseases (e.g., asthma, low birth weight, mental health, cardiopathy, obesity, and hypertension) (Alcock et al, 2015;Bowler et al, 2010;Gascon et al, 2016;Zhang et al, 2011). Second, higher risk of cancer, mortality, and low birth weight would be observed in neighborhood with more land delineated for industry (Cambra et al, 2011;Hendryx et al, 2012;Lopez-Cima et al, 2011).…”
Section: Public Health In Linkage To Land Usementioning
confidence: 99%
“…At present the association between folate insufficiency and the onset of placenta-mediated diseases, such as spontaneous abortion [58-65], preterm birth [66-75], foetal growth retardation [76-80], pre-eclampsia [81-88], abruptio placentae [89] and stillbirth [90] is still not entirely clear.…”
Section: Introductionmentioning
confidence: 99%